Assessment of major mental disorders in a German peripartum cardiomyopathy cohort. (10th September 2020) - Pfeffer, Tobias J.; Herrmann, Julian; Berliner, Dominik; König, Tobias; Winter, Lotta; Ricke‐Hoch, Melanie; Ponimaskin, Evgeni; Schuchardt, Sven; Thum, Thomas; Hilfiker‐Kleiner, Denise; Bauersachs, Johann; Kahl, Kai G.
Abstract: Aims: Peripartum cardiomyopathy (PPCM) is a heart disease affecting women during the last month of pregnancy or in the first months after delivery. The impact of the disease on mental health is largely unknown. Methods and results: Major mental disorders were assessed by a structured clinical interview in 40 patients with a confirmed PPCM diagnosis, and the data were compared with published prevalence in postpartum women. Circulating biomarkers associated with mental health, such as kynurenine, serotonin, and microRNA (miR)‐30e, were evaluated in PPCM and compared with matched healthy pregnancy‐matched postpartum controls (PP‐Ctrl). Major mental disorders were diagnosed in 65% (26/40) of the PPCM cohort. The prevalence for major depressive disorders was 4‐fold, for post‐traumatic stress disorder 14‐fold, and for panic disorder 6‐fold higher in PPCM patients compared with postpartum women without a PPCM diagnosis. Compared with PP‐Ctrl, PPCM patients displayed elevated levels of serum kynurenine ( P < 0.01), reduced levels of serum serotonin ( P < 0.05), and elevated levels of plasma miR‐30e ( P < 0.05). Conclusions: The majority of PPCM patients in the present cohort displayed mental disorders with a higher prevalence of major depressive disorders, post‐traumatic stress disorder (PTBS), and panic disorder, compared with postpartum women without a PPCM diagnosis. This higher prevalence was associated with an impaired tryptophan metabolism and elevated levels of the depression‐associated miR‐30e, suggesting a potential predisposition for mental disorders at the time of PPCM diagnosis. Consequently, physicians should be aware of the increased risk for mental disorders in PPCM patients, and psychiatric assessment should be included in the diagnosis and management of PPCM patients.